2007
DOI: 10.1038/sj.gene.6364422
|View full text |Cite
|
Sign up to set email alerts
|

Genes at human chromosome 5q31.1 regulate delayed-type hypersensitivity responses associated with Leishmania chagasi infection

Abstract: Visceral leishmaniasis (VL) caused by Leishmania chagasi is endemic to northeast Brazil. A positive delayed-type hypersensitivity skin test response (DTH þ ) is a marker for acquired resistance to disease, clusters in families and may be genetically controlled. Twenty-three single nucleotide polymorphisms (SNPs) were genotyped in the cytokine 5q23.3-q31.1 region IRF1-IL5-IL13-IL4-IL9-LECT2-TGFBI in 102 families (323 DTH þ ; 190 DTHÀ; 123 VL individuals) from a VL endemic region in northeast Brazil. Data from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 64 publications
3
47
0
3
Order By: Relevance
“…29 In a previous study , a similar situation was observed in an AVL-endemic area in the Municipality of Barcarena, Pará, around 150 km from the location of the present study; in that study, the AI profile corresponded to 73.2% of all cases of infection regarding their cumulative prevalence. Therefore, considering that delayed-type hypersensitivity 18 represents a strong expression of cellular immune 33,10 resistance against infection with L. (L.) i. chagasi, these results confirm that the vast majority (final distribution of the AI profile, 78.3%) of infected individuals in an endemic area are genetically resistant to infection. Also, considering that the SRI profile (final distribution, 15.1%) represents an evolutionary stage of infection with respect to the resistant pole (AI profile), the AI frequency could reach 90% in an endemic area.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…29 In a previous study , a similar situation was observed in an AVL-endemic area in the Municipality of Barcarena, Pará, around 150 km from the location of the present study; in that study, the AI profile corresponded to 73.2% of all cases of infection regarding their cumulative prevalence. Therefore, considering that delayed-type hypersensitivity 18 represents a strong expression of cellular immune 33,10 resistance against infection with L. (L.) i. chagasi, these results confirm that the vast majority (final distribution of the AI profile, 78.3%) of infected individuals in an endemic area are genetically resistant to infection. Also, considering that the SRI profile (final distribution, 15.1%) represents an evolutionary stage of infection with respect to the resistant pole (AI profile), the AI frequency could reach 90% in an endemic area.…”
Section: Discussionsupporting
confidence: 70%
“…Thereafter, these tests were only conducted on individuals who were found to be negative in the prevalence study and in the first incidence study (at 12 months). Therefore, individuals presenting reactivity only to MST, which represents a genetic characteristic of immunological resistance against the 18 infection , were removed from the subsequent assessments with this technique similarly to what was done in a 34 longitudinal study conducted in Sudan . Individuals presenting reactivity in both tests were tested again only for IFT, since it is unnecessary to inject new antigen loads into them, as would be the case with MST.…”
Section: Population and Study Designmentioning
confidence: 99%
“…L. donovani promastigotes stimulate IRF-1 expression in an lipophosphoglycan (LPG)-dependent manner in murine J774.1 cells (2). However, in a family study in a region of Brazil where visceral leishmaniasis (VL) is endemic, no genetic association was found between delayed-type hypersensitivity (DTH) positivity, a marker of resistance to L. chagasi, and single-nucleotide polymorphisms (SNPs) in Irf-1 (16). Irf-4 has been shown to play a T cell-intrinsic role in Th2 development in L. major (39).…”
mentioning
confidence: 94%
“…Interestingly, the 5q31 locus has been linked to several immune related disorders, including asthma/atopy (Meyers et al, 1994), inflammatory bowel disease (Lee et al, 2002), Crohn disease (Peltekova et al, 2004), Celiac disease (Latiano et al, 2007) and psoriasis (Friberg et al, 2006). Moreover, genes within the 5q31 locus have been suggested to regulate delayed-type hypersensitivity responses associated with Leishmania chagasi infection (Jeronimo et al, 2007). This region contains a cluster of cytokines, among which IL12B may play a critical role since it has been associated with some immune-related diseases.…”
Section: Genome Wide Linkage Analysis Of P Falciparum In Senegalmentioning
confidence: 99%